Analysis of Tweaking Quantum Dots Double Pane Window Solar Technology - Cheshta J. Khare, Sonali Shrivastava; Vikas Khare (Journal of Power Electronics and Devices, 2021)
The present scenario of electricity generation is mostly dependent on conventional energy sources, but these types of sources increase the contamination of greenhouse gases in the atmosphere. This type of problem is largely overcome by the advancement of solar energy technology and it is necessary to develop a material that has increased the efficiency of the photovoltaic panel. This paper assessed properties of Tweaking semiconductor nanostructures quantum dots double-pane solar window structure which is a promising class of well-designed material that is being developed for solar energy conversion technologies. This paper assessed the properties of tweaking quantum dots solar energy system in the terms of energy band, efficiency, and collection efficiency and also optimized efficiency of such type of system with the help of teaching learning-based algorithm and grasshopper optimization technique.